2016
DOI: 10.3389/fpsyg.2016.01064
|View full text |Cite
|
Sign up to set email alerts
|

Get Your Facts Right: Preschoolers Systematically Extend Both Object Names and Category-Relevant Facts

Abstract: There is an ongoing debate over the extent to which language development shares common processing mechanisms with other domains of learning. It is well-established that toddlers will systematically extend object labels to similarly shaped category exemplars (e.g., Markman and Hutchinson, 1984; Landau et al., 1988). However, previous research is inconclusive as to whether young children will similarly extend factual information about an object to other category members. We explicitly contrast facts varying in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…"My uncle gave this to me" participants systematically chose the other object. Holland, Mather, Simpson, and Riggs (2016) confirmed that children could recall this information:…”
Section: Successful Tool Innovationmentioning
confidence: 66%
“…"My uncle gave this to me" participants systematically chose the other object. Holland, Mather, Simpson, and Riggs (2016) confirmed that children could recall this information:…”
Section: Successful Tool Innovationmentioning
confidence: 66%